Lipoleiomyosarcoma an extremely unusual sarcoma of uterus: A case report - Jha, Abhimanyu; Sayami, Gita; Adhikari, Deepti (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Uterine lipoleiomyosarcoma is a heterologous sarcoma composed of variable proportions of malignant lipoblasts histologically corresponding to well differentiated liposarcoma and malignant smooth muscle cells corresponding to leiomyosarcoma. Finding of benign lipomatous component in a typical leiomyoma (lipoleiomyoma) is not an uncommon, however, lipoleiomyosarcoma is an extremely rare malignant tumor and only very few cases have been reported so far. We report a case of lipoleiomyosarcoma of uterine corpus in a postmenopausal woman presenting with lower abdominal pain and abdominal mass. Diagnosis of lipoleiomyosarcoma was confirmed by histopathological examination of hysterectomy specimen. This is the first case of lipoleiomyosarcoma of uterus reported from Nepal. Keywords: Lipoleiomyosarcoma, uterus, histopathology, unusual case. doi:10.3126/njog.v2i1.1482 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 67 - 70 May -June 2007